Progress and Criticism of Progress as a Characteristic of Modern Civilizations in the Work of Friedrich Nietzsche and Ludwig Wittgenstein - Ulrich Arnswald (Labyrinth: An International Journal for Philosophy, Value Theory and Sociocultural Hermeneutics)
Superficially, the proximity of Wittgenstein's work and its undisputed influence by Friedrich Nietzsche's ideas and concepts suggests that there are also overlaps in the large and in Nietzsche's work decisive field of progress and criticism of progress. The article tries to show that this is not the case. Despite all the overlaps that may exist between Friedrich Nietzsche and Ludwig Wittgenstein, these do not come to light in the concept of progress and the critique of progress. Both thinkers pursue a very different movement of thought; Wittgenstein sees Nietzsche's focus on the "idea of great progress" as a "delusion", which he does not consider to be expedient. Ludwig Wittgenstein explicitly distances himself here from the spirit that defined the prevailing European and American civilization in the 1930s. He does not succumb to the delusions of grandeur of new, higher-level civilization, but leaves progress as the constantly progressing background noise of any civilization.